2016
DOI: 10.1007/s13197-016-2228-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant, anti-diabetic and antilipemic potentials of quercetagetin extracted from marigold (Tagetes erecta L.) inflorescence residues

Abstract: Quercetagetin, the major flavonoid in marigold (Tagetes erecta L.) inflorescence residues was extracted and purified. The content of quercetagetin after the purification was 89.91 ± 0.26 %. The in vitro antioxidant activity of quercetagetin and its potential in controlling diabetes mellitus and obesity were investigated and compared to quercetin and rutin. The 50 % inhibitory concentration (IC 50 ) values of quercetagetin on scavenging 1, 1-diphenyl-2-picrylhydrazyl (DPPH), 2,2-azinobis-(3-ethylbenzothiazolin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 36 publications
(55 reference statements)
2
42
1
3
Order By: Relevance
“…Herbacetin has been described to have anti‐hyperglycaemic and anti‐hyperlipidemic properties (Veeramani et al , ). Quercetagetin exhibited strong in vitro antioxidant, anti‐diabetic and antilipidemic activities, having potential application for the treatment of obesity and diabetes (Wang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Herbacetin has been described to have anti‐hyperglycaemic and anti‐hyperlipidemic properties (Veeramani et al , ). Quercetagetin exhibited strong in vitro antioxidant, anti‐diabetic and antilipidemic activities, having potential application for the treatment of obesity and diabetes (Wang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature reported that aglycones have better antioxidant and anti‐inflammatory effects than diglycosides (Yang et al ., ). It was also reported that quercetin exhibits greater antioxidant activity than rutin, and therefore, it has potential benefits to treat diabetes and obesity (Wang et al ., ). The production of antioxidants by removing rhamnose from rutin was reported in literature (Cruz‐Zúñiga et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…However, pancreatic islet cells of diabetic rats treated with C. lobatus leaf methanol extracts appear normal. This suggests an inhibition of the toxic mechanisms involved in the alloxan-induced, oxidative stress-mediated destruction of pancreatic Islet cells by the antioxidant rich, flavonoid-containing C. lobatus extract inducing increased antioxidant enzyme activity, and consequently preserving Islet cells integrity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%